A map of the euro area financial system - Isabel Andersen; Antonio Sánchez Serrano (European Systemic Risk Board (ESRB), European System of Financial Supervision, 2024)
We present a methodology based on quarterly sectoral accounts to build a map of the euro area financial system. The map can be used to visualise existing cross-sectoral interconnections and exposures, to analyse how the main bilateral positions have evolved over time, and to understand how past episodes of financial stress affected balance sheet structures and inter-sectoral flows. We find that the euro area financial system was essentially bank-centric when it entered the global financial crisis, and only afterwards has the importance of investment funds, government debt and central banks increased substantially. In particular, investment funds are used by euro area economic agents to gain exposure to the rest of the world and vice versa. We also document weak dynamics since the global financial crisis in lending between euro area banks and non-financial corporations. Next, we look at the financial system during the global financial crisis and the outbreak of the COVID-19 pandemic, a further four episodes of financial stress (sovereign debt crisis, the US taper tantrum, the Brexit referendum, the start of Russia's invasion of Ukraine) and the monetary policy tightening between 2005 and 2007. While there are differences across them, we unveil interesting common features. The map can be useful in determining which sectors are resilient enough to absorb losses and whether they can serve as transmitters of stress. Finally, turning to liquidity, bank deposits, money market fund shares and securities financing transactions are key to ensure a smooth supply of liquidity and should continuously be on the radar of policymakers.
Keywords: G01; G1; G20; 330; Interconnections; flow of funds; financial crisis; financial intermediation; liquidity